Dietary Magnesium Intake Affects the Vitamin D Effects on HOMA-β and Risk of Pancreatic β-Cell Dysfunction: A Cross-Sectional Study - Gong, Rongpeng; Liu, Yuanyuan; Luo, Gang; Yang, Lixin (Frontiers in Nutrition, 2022)
Abstract: Background: Some studies have shown that，the circulating vitamin D (Vit D) concentration in the body plays a crucial role in regulating the pancreatic β-cell function. Meanwhile, the role of magnesium is important in the synthesis of Vit D, since it is an essential element for activating Vit D. Nevertheless, there remains insufficient studies concerning whether dietary Magnesium intake affects the association between Vit D and risk of pancreatic β-cell dysfunction. Hence, we designed this cross-sectional study to assess the effect of Magnesium intake alterations on the association between serum Vit D levels and the risk of pancreatic β-cell dysfunction. Methods: This large-scale cross-sectional study involves four cycles of National Health and Nutrition Examination Survey（NHANES）(2007–2014), with 4,878 participants in total. Groups were divided depending on the median daily intake of Magnesium, namely the low intake group (Magnesium intake <267 Magnesium/d) and the high intake group (Magnesium intake ≥ 267 Magnesium/d). By building multiple multivariate linear and logistics regression models, the associations between serum Vit D levels and HOMA-β, as well as between serum Vit D levels and the risk of pancreatic β-cell dysfunction were analyzed at different Magnesium intakes. Results: In this cross-sectional study, the serum Vit D level is independently correlated with the HOMA-β index (β: 0.65 (0.40–0.90)) and the risk of pancreatic β-cell dysfunction (OR: 0.95(0.92–0.98)). Moreover, such correlations are affected by different dietary Magnesium intakes (P for interaction <0.001).